Synthesis of Pyrroloquinones via a CAN Mediated Oxidative Free Radical Reaction of 1, 3-Dicarbonyl Compounds with Aminoquinones. (9th September 2013) - Nguyen, Thao; Nadkarni, Dwayaja; Dutta, Shilpa; Xu, Su; Kim, Sanghun; Murugesan, Srinivasan; Velu, Sadanandan
Abstract : Pyrroloquinone ring systems are important structural units present in many biologically active molecules including a number of marine alkaloids. For example, they are found in a series of marine metabolites, such as tsitsikammamines, zyzzyanones, wakayin, and terreusinone. Several of these alkaloids have exhibited antimicrobial, antimalarial, antifungal, antitumor, and photoprotecting activities. Synthesis of pyrroloquinone unit is the key step in the synthesis of many of these important organic molecules. Here, we present a ceric (IV) ammonium nitrate (CAN) mediated oxidative free radical cyclization reaction of 1, 3-dicarbonyl compounds with aminoquinones as a facile methodology for making various substituted pyrroloquinones. 1, 3-dicarbonyl compounds used in this study are ethyl acetoacetate, acetylacetone, benzoyl acetone, and N, N -dimethyl acetoacetamide. The aminoquinones used in this study are 2-(benzylamino)naphthalene-1, 4-dione and 6-(benzylamino)-1-tosyl-1 H -indole-4, 7-dione. The yields of the synthesized pyrroloquinones ranged from 23–91%.